Emotional and Cognitive Modulation of Cybersickness: The Role of Pain Catastrophizing and Body Awareness. (March 2019) - Mittelstädt, Justin Maximilian; Wacker, Jan; Stelling, Dirk
Objective: The goal was to investigate the influence of the tendency to catastrophize somatic symptoms and body awareness on motion-related sickness. Background: Influences of emotional and cognitive-evaluative processes on the genesis of motion sickness or cybersickness have rarely been investigated. Brain imaging studies showed activation during cybersickness, resembling the pattern found for pain processing. Two aspects often investigated in this context are pain catastrophizing and body awareness. The present two studies investigated the relationship of motion-related sickness to two tendencies involved in pain processing: pain catastrophizing and body awareness. Method: In the first study, 115 participants reported their motion sickness history, pain catastrophizing, and body awareness. In the second study, 40 participants were exposed to a virtual reality and reported their experience of cybersickness as well as their pain catastrophizing and body awareness. Results: Pain catastrophizing was positively correlated to motion sickness history and cybersickness. Body awareness did not show a linear effect on motion sickness history or cybersickness. However, the interaction effect of pain catastrophizing and body awareness was significant in both studies. Conclusion: Pain catastrophizing seems to have a detrimental effect on cybersickness symptoms. Body awareness moderated the relationship in the sense that the combination of high pain catastrophizing and low body awareness lead to the highest sickness levels. Application: Affective and cognitive modulation of cybersickness symptoms should be considered when exposing risk groups to motion-related adverse stimuli.